I NEED HELP!!!

(a ± b) = a^{2} ± 2ab +
b^{2}

4x^{2} + 24x + y^{2} - 10y - 3 = 0

4(x^{2} + 6x) + (y^{2} -10y) = 3

*4*(x^{2} + 2 · x · 3 + ** 9)** + (y

^{2}- 2 · 5 · y +

**) =**

*25***+**

*36***+ 3**

*25*↑ times ↑ ↑

= 36 ↑ ↑

add 25 to the both sides

4(x + 3)

^{2}+ (y + 5)

^{2}= 64

4(x + 3)

^{2}(y + 5)

^{2}

————— + ———— = 1

64 64

**(x + 3)**

^{2}(y + 5)^{2}**————— + ———— = 1**

**8 64**

## Comments

I tried that but I don't understand how to do it. the problem is 4x

^{2 }+24x +y^{2}-10y-3=0